Spouse selection among the children of european immigrants : a comparison of marriage cohorts in the 1960 census - Kalmijn, M.
tbls., gráfs.
pp. 51-78
Keywords: Matrimonio; Costumbres Matrimoniales; Educacion para la Vida Familiar; Inmigrantes; Europeos; Analisis por Cohortes; Estados Unidos de America